Educating deaf students : from research to practice - Marschark, Marc; Lang, Harry G.; Albertini, John A. (John Anthony), 1945- (Oxford ; New York : Oxford University Press, 2002)
"Over the past decade there has been a significant increase in interest from educators and the general public about deafness, special education, and the development of children with special needs. The education of deaf children in the United States has been seen as a remarkable success story around the world, even while it continues to engender domestic debate." "In Educating Deaf Students: From Research to Practice, Marc Marschark, Harry G. Lang, and John A. Albertini set aside the politics, rhetoric, and confusion that often accompany discussions of deaf education. Instead they offer an accessible evaluation of the research literature on the needs and strengths of deaf children and on the methods that have been used - successfully and unsuccessfully - to teach both deaf and hearing children."--Jacket
Educational basics. Educating deaf students -- Lessons from history -- Characteristics of deaf learners -- Education begins at home. Educational processes and programs. Language development and deaf children -- Cognitive development and deaf children -- Educational programs and philosophies -- Reading, writing, and literacy -- Teaching and the curriculum. Conclusion. Looking ahead while glancing back.
Includes bibliographical references (pages 237-262) and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Deaf people -- Education; Deaf children -- Education; Deaf children -- Language; Deaf children -- Means of communication; Personnes sourdes -- Éducation.; Enfants sourds -- Éducation.; Enfants sourds -- Langage; Enfants sourds -- Moyens de communication; EDUCATION -- Special Education -- Physical Disabilities; Deaf children -- Education; Deaf children -- Language; Deaf children -- Means of communication; Deaf -- Education